Electrochemical synthesis of carbon-metal fluoride nanocomposites as cathode materials for lithium batteries - M. Helen; Maximilian Fichtner; M. Anji Reddy (Electrochemistry Communications, 2020)
Herein we have demonstrated an electrochemical method for the synthesis of carbon-metal fluoride nanocomposites (CMFNCs). Electrochemical intercalation of transition metal ions into graphite fluoride (CFx) resulted in the formation of CMFNCs. As a proof-of-concept, we have synthesized C-FeF2 and C-NiF2 nanocomposites by the electrochemical intercalation of Fe2+ and Ni2+ into CFx from corresponding non-aqueous electrolytes. The C-FeF2 and C-NiF2 nanocomposites synthesized by this method showed high reversible capacity and cycling stability compared to chemically synthesized analogs as cathode materials for lithium batteries. The reversible capacity of chemically synthesized C-FeF2 is 181 mAh g−1, whereas electrochemically synthesized material is 349 mAh g−1 after 20 cycles. The better cycling performance of electrochemically synthesized C-FeF2 was attributed to the homogeneous distribution of FeF2 nanoparticles within the carbon matrix enabled by the electrochemical intercalation of Fe2+. The electrochemical method described here is emission-free, cost-effective, occurs at room temperature, and extendable to the synthesis of several other CMFNCs. Moreover, it might provide new avenues for the synthesis of advanced functional materials.